2007
DOI: 10.1080/11762320701455807
|View full text |Cite
|
Sign up to set email alerts
|

Static Standing Trunk Sway Assessment in Amputees – Effects of Sub‐Threshold Stimulation

Abstract: Sub‐threshold electrical stimulation can enhance the sensitivity of the human somatosensory system to improve the balance control capability of elderly was shown in recent rehabilitation articles. The purpose of this study was to evaluate the postural sway of trans‐tibial amputees when performing single leg quiet standing on firm surface. Four unilateral trans‐tibial amputees who consecutively wore prosthetics over 2 years were recruited in this study. Subjects performed single leg quiet standing trails with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 6 publications
0
4
1
Order By: Relevance
“…The results from the current study showed a large bias toward recruiting males in research in this area. The reported 26.4% of female lower limb prosthesis users participating in studies was lower than what has been reported in a highly regarded national amputation registry (SwedeAmp; 39%), 234 as well as in previous research (34.5%–38.4%) such as Claessen et al 235 and Ziegler-Graham et al 236 The present authors think it is noteworthy that, of the (n = 161) articles reporting characteristics on sex in the balance articles in Supplemental Table (Supplemental Digital Content 2, http://links.lww.com/POI/A170) 12-14,19-23,25,26,28,29,31-42,44,45,47,48,50-56,58,59,62-69,71-75,77-85,88-90,92,94-102,105-120,122-136,138,140-153,155,157-165,167-179,181-184,186-198,230,231 and the (n = 62) articles of balance confidence, 4,6,8,14,44,71,78,81,83,94,134,138,143,145,147,148,150,151,153,155,157,159,163,165,172,175-178,183,193,196,199-203,205-209,211-229 29.2% and 19.4% respectively, included male sex exclusively. There were only (n = 2) studies with female participants, one balance article 231 and one balance confidence article.…”
Section: Discussioncontrasting
confidence: 51%
See 4 more Smart Citations
“…The results from the current study showed a large bias toward recruiting males in research in this area. The reported 26.4% of female lower limb prosthesis users participating in studies was lower than what has been reported in a highly regarded national amputation registry (SwedeAmp; 39%), 234 as well as in previous research (34.5%–38.4%) such as Claessen et al 235 and Ziegler-Graham et al 236 The present authors think it is noteworthy that, of the (n = 161) articles reporting characteristics on sex in the balance articles in Supplemental Table (Supplemental Digital Content 2, http://links.lww.com/POI/A170) 12-14,19-23,25,26,28,29,31-42,44,45,47,48,50-56,58,59,62-69,71-75,77-85,88-90,92,94-102,105-120,122-136,138,140-153,155,157-165,167-179,181-184,186-198,230,231 and the (n = 62) articles of balance confidence, 4,6,8,14,44,71,78,81,83,94,134,138,143,145,147,148,150,151,153,155,157,159,163,165,172,175-178,183,193,196,199-203,205-209,211-229 29.2% and 19.4% respectively, included male sex exclusively. There were only (n = 2) studies with female participants, one balance article 231 and one balance confidence article.…”
Section: Discussioncontrasting
confidence: 51%
“…13,71-107 Less common were single-limb measurements. 79,92,94,108-113 The equipment used across studies varied, but the most common was multiple force plates (Figure 2). 12,19-48,51-60,62-70,114-117 Motion capture systems were also common.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations